Techniques of Translating Adele’s 25 Album into Indonesian and The Naturalness Quality (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2019)
This research focuses on analyzing the use of translation techniques and the naturalness of the translated lyrics. The objectives of the study were to investigate the translation techniques used to translate song lyrics and to identify the naturalness in translated lyrics of Adele's 25 album songs. This research was done qualitatively. This research applied the translation technique classification proposed by Molina and Albir (2002:509-511) and the naturalness assessment proposed by Nababan (2012). Data analysis was done by comparing the original language and the translated lyrics version to find out the most used of translation techniques. The rater survey was also done by asking 20 respondents to find out the naturalness level of the translated lyrics. The results of the study showed that there were 276 data of the translated lyrics and 11 translation techniques found in this research. Literal translation technique was the most frequent used, followed by Linguistic compression. Some other translation techniques were used moderately such as, Established equivalent, reduction, and discursive creation. The rest techniques were used in low frequency such as modulation, amplification, compensation, linguistic amplification, transposition, and particularization. In terms of naturalness assessed by twenty respondents found that around 61.95% of the data were considered natural translation, 28.80% were less natural and 9.23% were unnatural. The translation techniques with the highest naturalness were Linguistic amplification technique with a percentage 68.18%, particularization was contributing most to less natural translation with percentage 45%, and the transposition technique was contributing most to unnatural translation with percentage 23%. From the data, it can be concluded that the translated lyrics of Adele's 25 album were mostly natural. Keywords: Song, Lyric, Translation Techniques, Naturalness